Gut Microbiota – A Potential Contributor in the Pathogenesis of Bipolar Disorder - Zhang, Peifen; Kong, Lingzhuo; Huang, Huimin; Pan, Yanmeng; Zhang, Danhua; Jiang, Jiajun; Shen, Yuting; Xi, Caixi; Lai, Jianbo; Ng, Chee H.; Hu, Shaohua (Frontiers in Neuroscience, 2022)
Bipolar disorder (BD) is one of the major psychiatric disorders that is characterized by recurrent episodes of depression and mania (or hypomania), leading to seriously adverse outcomes with unclear pathogenesis. There is an underlying relationship between bacterial communities residing in the gut and brain function, which together form the gut-brain axis (GBA). Recent studies have shown that changes in the intestinal flora have been observed in a large number of BD patients, so the axis may play a role in the pathogenesis of BD. This review summarizes the composition and changes of intestinal flora in patients with BD, and briefly analyzes and summarizes existing studies on the relationship between the GBA and brain function, as well as adjuvant treatments of BD based on the GBA regulation, and further explores the possible role of GBA-related pathway in the pathogenesis of BD, in order to provide new ideas for the future etiology research and drug development.